Reduced graphene oxide/nano-Bioglass composites: processing and super-anion oxide evaluation. Issue 24 (17th February 2016) - Ashok raja, C.; Balakumar, S.; Durgalakshmi, D.; George, R. P.; Anandkumar, B.; Kamachi Mudali, U.
Abstract : 45S5 Bioglass with a mean particle size in the nano regime was synthesized and fabricated with rGO sheets using three different strategies. Abstract : 45S5 Bioglass with a mean particle size in the nano regime were synthesized and fabricated with rGO sheets using three different strategies. The fabricated nanocomposites were analysed for their bond formation and defects. Morphology, size and distribution of n-BG particles on rGO were visualised. An attempt to understand the superoxide anion production by n-BG particles, rGO and its nanocomposites was made.